COMPARATIVE ANALYSIS OF THE MALE AND FEMALE LEXICON IN ENGLISH AND UZBEK LANGUAGES. - Nurulloyeva Charos Ubaydullayevna (TADQIQOTLAR.UZ, 2024)
Annotation: This article investigates the differences and similarities in the male and female lexicon in English and Uzbek languages, focusing on gender-specific vocabulary, communication styles, and cultural influences. It analyzes how societal roles and cultural norms shape language use among men and women in both linguistic contexts.